The Value of Prognostic Nutritional Index in Follicular Lymphoma. (February 2019) - Lee, Shing Fung; Ng, Ting Ying; Wong, Frank Chi Sing
Abstract : Objectives: Previous studies reported that prognostic nutritional index (PNI), a marker of host inflammatory and nutritional status, is associated with prognoses in a number of cancer types. Thus, we investigated PNI at diagnosis as a prognostic factor in FL. Methods: We reviewed FL patients in Tuen Mun Hospital, Hong Kong from 2000 to 2014 (n=88). PNI was calculated by serum albumin (g/L)+5×absolute lymphocyte count (10 9 /L). We determined the best PNI cut-off value using receiver-operating characteristic curves. The extent to which progression-free survival (PFS) and overall survival differed by PNI cut-off was assessed using Kaplan-Meier and log-rank tests. Cox proportional hazards model was utilized to adjust for covariates. Results: The best cut-off value for PNI was determined to be 45. Patients with high PNI (>45) had a higher complete response (CR) rate after primary treatment, 46 of 61 (75.4%) patients with high PNI had CR, compared with 10 of 23 (43.5%) for low PNI (2-sample test of proportions P -value=0.006). Further, higher PNI at relapse as a continuous variable was associated with superior postprogression survival with a hazard ratio (HR) 0.88 (95% confidence interval [CI], 0.81-0.96). In multivariate analysis, high PNI at diagnosis had superior PFS (adjusted HR of 0.37; 95% CI, 0.15-0.93). Conclusions: PNI was shown to be independent prognostic factor of PFS in FL. It is a cheap and widely available biomarker. Future study is needed to validate its prognostic value and clinical utility in a prospective cohort. Abstract : Supplemental Digital Content is available in the text.